Digital economy: Basic aspects and the case of Serbia - Đorić Žarko (Ekonomski Pogledi, 2020)
The global economy, strong competition, changing the nature of the workforce and consumer sophistication have influenced the need to transform the traditional economy into a digital economy, as a new phenomenon that permeates almost all economic and social processes in one society. The aim of the research is to point out the nature and characteristics of the digital economy, as well as its achieved level of development in the Republic of Serbia. The digital economy, showing its global nature, "leaked" to us, and the very process of digitization by the government was set as one of the three pillars of Serbia's development (in addition to economic growth and education). Using case-study method we found that Serbia is still very far from a massive digital lifestyle. Engaging in an ambitious regulatory reform process in the field of telecommunications: all digital services, applications and content depend on the availability of fast and secure infrastructure.